Long-term outcomes from the Phase II L-MIND study of tafasitamab (MOR208) plus lenalidomide in patients with relapsed or refractory diffuse large B-cell lymphoma - Duell, Johannes; Maddocks, Kami J; González-Barca, Eva; Jurczak, Wojciech; Liberati, Anna Marina; De Vos, Sven; Nagy, Zsolt; Obr, Aleš; Gaidano, Gianluca; Abrisqueta, Pau; Kalakonda, Nagesh; André, Marc; et al. (Haematologica, 2021)
Tafasitamab (MOR208), an Fc-modified, humanized, anti-CD19 monoclonal antibody, combined with the immunomodulatory drug lenalidomide was clinically active with a good tolerability profile in the open-label, single-arm, phase II L-MIND study of patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) ineligible for autologous stem-cell transplantation. To assess long-term outcomes, we report an updated analysis with ≥35 months' follow-up. Patients were aged >18 years, had received one to three prior systemic therapies (including ≥1 CD20-targeting regimen) and Eastern Cooperative Oncology Group performance status 0-2. Patients received 28-day cycles of tafasitamab (12 mg/kg intravenously), once weekly during cycles 1-3, then every 2 weeks during cycles 4-12. Lenalidomide (25 mg orally) was administered on days 1-21 of cycles 1-12. After cycle 12, progression-free patients received tafasitamab every 2 weeks until disease progression. The primary endpoint was best objective response rate. After ≥35 months' follow-up (data cut-off: October 30, 2020), the objective response rate was 57.5% (n=46/80), including a complete response in 40.0% of patients (n=32/80) and a partial response in 17.5% of patients (n=14/80). The median duration of response was 43.9 months (95% confidence interval [95% CI]: 26.1-not reached), the median overall survival was 33.5 months (95% CI: 18.3-not reached) and the median progression-free survival was 11.6 months (95% CI: 6.3-45.7). There were no unexpected toxicities. Subgroup analyses revealed consistent long-term efficacy results across most subgroups of patients. This extended follow-up of L-MIND confirms the long duration of response, meaningful overall survival, and well-defined safety profile of tafasitamab plus lenalidomide followed by tafasitamab monotherapy in patients with relapsed/refractory diffuse large B-cell lymphoma ineligible for autologous stem cell transplantation. ClinicalTrials.gov identifier: NCT02399085.
Keywords: výsledek terapie; lenalidomid; autologní transplantace; Lymphoma, Large B-Cell, Diffuse; Lenalidomide; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Transplantation, Autologous; Treatment Outcome; transplantace hematopoetických kmenových buněk; lidé; difúzní velkobuněčný B-lymfom; Antineoplastic Combined Chemotherapy Protocols; Humans; Hematopoietic Stem Cell Transplantation; protokoly protinádorové kombinované chemoterapie